REALISME MAGIS DALAM CERPEN ARAJANG KARYA KHRISNA PABICHARA: KONSEP KARAKTERISTIK REALISME MAGIS WENDY B. FARIS - , HASBI ASGA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The focuse of this research is magical realism phenomenon in Modern Indonesian short stories which departing from the relationship between indonesian literature and western, as an effect of literary interaction continously between Indonesian and western. The effect of this world literary interaction is there is a tendency that Indonesian short stories are lifted back the voices that marginalized in western empirical persective. In every image how magical realism works seen as irrational thing such as myth, living legend, fairy tales, and another mystical things that comes from one society tradition. Khrisna Pabichara is one of indonesian short story writer who lifted back the voice of marginal that happened in Bugis -Makassar culture, through his work entitled Arajang. He responded some issue about social context, ideology, and discursive that expressed by magical realism narrative technique. The concept of magical realism in Wendy B. Faris in his book entitled Ordinary Enchantments Magical Realism AndRemystifiction of Narratives is used in this research, through several stages. First, by identified and classified the elements according to the magical realism characteristics that have been formulated by Faris, and followed by generalized the relation between elements and element structure functions. The next stages is reaching the social context, ideology, and discursive that already pictured in Arajang short story. Magical element as a traditional discourse is used by the author as a different perspective in the middle of modern era. Which pictured by the figures, events, and objects that represented the real world. The author also voiced the main issue that is modernism in Bugis Makassar culture